(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2026)
The relationship between object theater and other artistic forms that participate in the objectual dynamics, awakens investigative concerns. This comparative analysis likens concepts derived from object theater with the practice of a branch of illusionism called close-up magic. In it, the artist and the audience interact in an intimate way. The use of everyday objects intensifies the astonishing effect, which is the obligatory purpose of all magic games. Actor, manipulator, character, person, body and object system are the axes selected to establish confluences and divergences between both artistic specialties. This article is an advance of a research in progress for the doctoral thesis in Arts of the UNA, Universidad Nacional de las Artes, Bs. As.